The reducing effect of visuospatial cognitive load on alcohol craving in problematic drinkers - Mi-Young Park; InGyeong Kim; MinJae Kim; Gi-Eun Lee; Jang-Han Lee (Frontiers in Psychology, 2026)
Introduction Alcohol use disorder is a significant global health concern, and craving serves as a central mechanism sustaining problematic drinking and a critical, cognitively accessible intervention target. This study examined whether visuospatial working memory depletion could reduce alcohol craving and attentional bias in problematic drinkers by disrupting the elaboration of intrusive alcohol-related thoughts. Methods Following screening with the Alcohol Use Disorders Identification Test (AUDIT; score ≥ 12), 50 problematic drinkers were randomized to a Load or No Load Group. The Load Group completed the Corsi block-tapping task and the No Load Group a matched no-load control task. Self-reported craving and eye-tracking indices of attentional bias were assessed before and after the intervention. Early attentional orienting was indexed by time to first fixation and late attentional maintenance by total fixation duration to simple and complex alcohol stimuli. Five participants were subsequently excluded for poor eye-tracking data quality. The final sample comprised 45 (Load Group n = 23, No Load Group n = 22). Results The Load Group showed significantly reduced Alcohol Urge Questionnaire (AUQ) scores post-task. While no significant differences emerged in early attentional bias, the Load Group showed suppressed late attentional bias toward alcohol cues, whereas the No Load Group showed a significant increase. Discussion This indicates that visuospatial cognitive load blocked the progressive strengthening of attention toward alcohol cues. The load manipulation selectively suppressed late, top-down attentional maintenance, the component most closely linked to craving and relapse risk, while leaving automatic orienting intact. This pattern therefore suggests that the load manipulation acts on the elaboration stage through which alcohol cues develop into sustained urge. These findings suggest that visuospatial cognitive load may function as a brief, non-invasive, and self-administered craving intervention that could serve as an accessible adjunct to, rather than a substitute for, formal treatment, with potential relevance to other addictive behaviors characterized by heightened cue salience.